What Is the Role of Ethics Committees in AI Healthcare? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
As artificial intelligence (AI) continues to permeate every facet of healthcare, from diagnostics and treatment personalization to patient care management, t...
Keywords: AI Ethics in Healthcare; Ethics; Committees; Healthcare; Artificial Intelligence; Machine Learning; Clinical Decision Support